Some of the Aspects of Bilingual Education in Modern Guatemala - Irina B. Kotenyatkina; Anastasia A. Borzenkova; Maria Radovich (Polylinguality and Transcultural Practices, 2019)
The present article demonstrates the development of the concept of bilingual education in Guatemala, caused by the transition to a new type of society: the knowledge society, where the education is considered as the main principle of economic growth. The special attention is paid to the specific needs of indigenous children from the linguistic and cultural points of view, as well as to the fact that the languages spoken by the local population are not being used as a tool during the teaching process. The article points out that the intercultural communication, as a primary principle of bilingual education, allows to overcome difficult sociolingustic conditions and favours the processes of the personality formation, while offering the possibilities of shaping individuals having both Spanish and indigenous languages and cultures as a basis.